PENGAMANAN FILE DOKUMEN MENGGUNAKAN KOMBINASI METODE SUBTITUSI DAN VIGENERE CIPHER - Budi, Sarwo; Purba, Arif Budimansyah; Mulyana, Jajang (ILKOM Jurnal Ilmiah, 2019)
Cryptography is a method of securing data using algorithms that have been developed continuously until now. Cryptography offers security in the form of data confidentiality, for example the confidentiality of data generated through encryption algorithms that scrambles personal information so that it cannot be read or solved by unauthorized parties. One of them is the substitution algorithm and the vigenere cipher is a classic method used for data security. The combination of these algorithm methods becomes a solution for double security as file protection. By using a cryptographic application for data security, the combination of the two method algorithms produces a data file that provides more security to the text file so that it is not easy and difficult to solve.